2021
DOI: 10.1039/d0ay01992e
|View full text |Cite
|
Sign up to set email alerts
|

Supported bilayer membranes for reducing cell adhesion in microfluidic devices

Abstract: The high surface area-to-volume ratio of microfluidic channels makes them susceptible to fouling and clogging when used for biological analyses,including cell-based assays. We evaluated the role of electrostatic and van...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For instance, in microfluidic cell sorters that sort sickle red blood cells based on their deformability, clogging leads to greater unpredictability in the device behaviour. Previous studies have shown that clogging contributes to a faster fouling of the device [6][7][8][9][10]. Investigating the detailed nature of clogging in these microfluidic devices provides an opportunity to gain a deeper understanding of their properties and how their performance can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in microfluidic cell sorters that sort sickle red blood cells based on their deformability, clogging leads to greater unpredictability in the device behaviour. Previous studies have shown that clogging contributes to a faster fouling of the device [6][7][8][9][10]. Investigating the detailed nature of clogging in these microfluidic devices provides an opportunity to gain a deeper understanding of their properties and how their performance can be improved.…”
Section: Introductionmentioning
confidence: 99%
“… 16 18 Owing to their antifouling properties and the diversity in lipid species chemistry, SLBs have been used to modulate surface properties at the nanoscopic level. 19 24 In this work, we explore the relevance of lipid bilayer coatings for electrostatic trapping of single molecules in solution. Such coatings are advantageous in that they offer tunability of both the sign and magnitude of the surface electrical charge in device-based systems where surface interactions play a strong role.…”
Section: Introductionmentioning
confidence: 99%
“…Supported lipid bilayers (SLBs) are self-assembled two-dimensional thin-film coatings composed of a single phospholipid bilayer resting on or near a solid support . The ability of SLB systems to mimic native cell membranes has been successfully employed in fundamental biophysical studies for several decades. , Specifically, SLB systems serve as a useful tool for studying cell adhesion and repulsion, peptide–cell interactions, cell–surface interactions, and membrane properties in general. Given their unique properties, such as biological inertness, amphiphilicity, and ability to serve as matrixes for surface immobilization, SLBs have found applications in biosensors, drug delivery, and medical diagnostics. Furthermore, ongoing advances in microfluidics, biosensor design, and micro- and nanofabrication have opened up new application avenues for nanostructured SLBs. Owing to their antifouling properties and the diversity in lipid species chemistry, SLBs have been used to modulate surface properties at the nanoscopic level. In this work, we explore the relevance of lipid bilayer coatings for electrostatic trapping of single molecules in solution. Such coatings are advantageous in that they offer tunability of both the sign and magnitude of the surface electrical charge in device-based systems where surface interactions play a strong role …”
Section: Introductionmentioning
confidence: 99%